Ctenophora sinensis: a new diatom species (Bacillariophyta) from China with comments on its structure, nomenclature and relationships - Liu, Bing; Williams, David M.; Liu, Zhu-Xiang; Chen, Jin-Hua (Phytotaxa, 2020)
Lake Qinghai is an ancient brackish water lake in the Qinghai province of China. A number of endemic diatom species have already been discovered and described from the lake. This study describes another new endemic diatom species: Ctenophora sinensis sp. nov. Ctenophora sinensis has the following features: (1) frustule and valve are lanceolate; (2) the central area is slightly buttressed internally; (3) its areolae have both outside sieve-like closing plates and inside hymenate occlusions; (4) an apical hyaline field exists near each rimoportula; (5) a pseudoseptum is always presents at each pole; and (6) the cingulum has a 4:2 configuration of girdle bands in normal vegetative cells. Some remarks are provided on the nomenclature of Ctenophora and a few comments on the relationships of the genus.